A New Side Effect of Intravitreal Dexamethasone Implant (Ozurdex®) - Erdem Eris; Gurkan Erdogan; Irfan Perente; Gokhan Demir; Burcin Kepez Yildiz; Ebru Demet Aygit (Case Reports in Ophthalmological Medicine)
Dexamethasone implant, 0,7 mg (Ozurdex, Allergan, Inc., Irvine, CA, USA), is drug mostly used in the treatment of the diabetic macular edema and edema related to retinal vein occlusion. By reporting this case we aimed to report a new side effect of 0.7 mg intravitreal dexamethasone implant that has not been reported in the literature before.